Postdigital Performance - Causey, Matthew (Theatre journal (Washington, D.C.), 2016)
Theatre Journal's 1999 special issue on "Theatre and Technology" serves as a useful starting point for a consideration of the significant changes taking place in theatre and performance of current postdigital culture. This essay briefly considers the ontological questions and identity issues that arose during the introduction of media and digital studies in the fields of theatre and performance. The original ontological questions regarding media and performance and the strategies of identity formation and subject positions within electronic communications have been significantly altered regarding the hegemony and ubiquitous affects of the digital in contemporary life. A zone of indistinction marks the ontological structures of media and performance while the issues regarding identity and subjectivity in the spaces of technology are challenged in electronic communications, commerce, and capitalism. The essay defines the affects of the postdigital condition while exploring the developing aesthetics and politics of a "postdigital performance." Examples of such performance include the installation and video work of Ryan Trecartin and Lizzie Fitch, immersive theatre company ANU Productions, and hybrid performance works by Blast Theory and the National Theatre of Wales. These works are argued as processes of "thinking digitally," which is a means to engage and resist current electronic cultures of control, be they social, economic, or technological.